Single-crystal and humidity-controlled powder diffraction study of the breathing effect in a metal–organic framework upon water adsorption/desorption. Issue 45 (13th May 2016) - Aríñez-Soriano, Javier; Albalad, Jorge; Vila-Parrondo, Christian; Pérez-Carvajal, Javier; Rodríguez-Hermida, Sabina; Cabeza, Aurelio; Juanhuix, Jordi; Imaz, Inhar; Maspoch, Daniel
Abstract : Water adsorption/desorption-triggered single-crystal to single-crystal transformations in a MOF are studied. Abstract : Herein we report a study on water adsorption/desorption-triggered single-crystal to single-crystal transformations in a MOF, by single-crystal and humidity-controlled powder X-ray diffraction and water-sorption measurements. We identified a gate-opening effect at a relative humidity of 85% upon water adsorption, and a gate-closure effect at a relative humidity of 55 to 77% upon water desorption. This reversible breathing effect between the "open" and the "closed" structures of the MOF involves the cleavage and formation of several coordination bonds.